2015
DOI: 10.4314/ajid.v10i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiotic susceptibility pattern of ESBL producing Klebsiellae isolated from clinical specimens in a Nigerian tertiary hospital

Abstract: Background: Infection by Extended Spectrum Beta Lactamases (ESBLs) producing bacteria is a threat to man as a consequence of treatment challenges. This study evaluated the prevalence and antimicrobial susceptibility pattern of ESBL producing Klebsiellae (EPK) in clinical specimens at the University of Ilorin Teaching hospital, Ilorin (UITH), Nigeria. Methods: ESBL production was assayed using Double Discs Synergy Test (DDST). Antimicrobial susceptibility was performed by Modified KirbyBaeur method with the org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
4
4
0
Order By: Relevance
“…The ESBL-producing isolates observed in this study were E. coli and Klebsiella sp. ; this is in agreement with other studies that reported that both isolates contain ESBL enzyme [13,18]. ESBL has been reported to confer resistance to all β-lactam antibiotics except cephamycin and carbapenems [29].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The ESBL-producing isolates observed in this study were E. coli and Klebsiella sp. ; this is in agreement with other studies that reported that both isolates contain ESBL enzyme [13,18]. ESBL has been reported to confer resistance to all β-lactam antibiotics except cephamycin and carbapenems [29].…”
Section: Discussionsupporting
confidence: 93%
“…ESBL-producing bacterial isolates have been found in both hospital and community settings [6,16]. Furthermore, ESBL-producing enterobacteriaceae may acquire resistance to non-β-lactam antibiotics in the community [17][18]. The present study determines the occurrence of ESBL among Gram-negative bacilli (GNB) isolated from the urine of apparently heathy individuals at the Obafemi Awolowo University.…”
Section: Introductionmentioning
confidence: 95%
“…also had considerable resistance to other antibiotics including ofloxacin (94.4%), nitrofurantoin (72.2%) and 88.9% resistance to nalidixic acid, gentamicin and levofloxacin. This is similar to the findings of Fadeyi et al [6] and Humayun et al [21] that reported the resistance of Klebsiella spp. to fluoroquinolone, aminoglycoside and sulfamethoxazole in Nigeria and Pakistan respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Strains were resistant to fluoroquinolones, carbapenem, third and fourth generation cephalosporins. In a similar study, Fadeyi et al [6] in Nigeria reported Klebsiella spp. of clinical origin that displayed high resistance to ceftazidime (100%), cefotaxime (94.0%), ciprofloxacin (70.0%) and trimethoprim-sulphamethoxazole (92.0%).…”
Section: Introductionmentioning
confidence: 67%
“…The udy showed that 39 -90% of seven common bacterial isolates were resistant to Amoxicillin + Clavulanic acid, similar high level of microbial resistance was also observed for Cotrimoxazole [29 -84%], Tetracycline [17 77%], Ceftriaxone [6 -50%] and Genta -40%]. The high level of antibiotic resistance level in this study is comparable to many other studies, though differences exist in the magnitude [58][59][60][61][62].…”
Section: Fig 2 Age Distributionsupporting
confidence: 83%